The arts of disruption allegory and Piers Plowman - Zeeman, Nicolette 1956- (Oxford University Press, 2020)
The monograph series Oxford Studies in Medieval Literature and Culture showcases the plurilingual and multicultural quality of medieval literature and actively seeks to promote research that not only focuses on the array of subjects medievalists now pursue - in literature, theology, and philosophy, in social, political, jurisprudential, and intellectual history, the history of art, and the history of science - but also that combines these subjects productively. It offers innovative studies on topics that may include, but are not limited to, manuscript and book history; languages and literatures of the global Middle Ages; race and the post-colonial; the digital humanities, media and performance; music; medicine; the history of affect and the emotions; the literature and practices of devotion; the theory and history of gender and sexuality, ecocriticism and the environment; theories of aesthetics; medievalism.0The Arts of Disruption: Allegory and Piers Plowman offers a series of new readings of the allegorical poem Piers Plowman: but it is also a book about allegory. It argues not just that there are distinctively disruptive 'arts' that occur in allegory, but that allegory, because it is interested in the difficulty of making meaning, is itself a disruptive art. The book approaches this topic via the study of five medieval allegorical narrative structures that exploit diegetic conflict and disruption. Although very different, they all bring together contrasting descriptions of spiritual process, in order to develop new understanding and excite moral or devotional change. These five structures are: the paradiastolic 'hypocritical figure' (such as vices masked by being made to look like 'adjacent' virtues), personification debate, violent language and gestures of apophasis, narratives of bodily decline, and grail romance
Keywords: Langland, William -- 1332-1400 -- Piers Plowman; Allegorie